The Effect Of Ferritin Concentration As A Result Of Iron Deficiency and Its Effect On Corona Patients - Maha Jalil Jabbar; Hatef Rahim Mahdi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Ferritin is considered a protein that contains iron and includes two types of subunits: ferritin light chain (FTL) and ferritin heavy chain (FTH), which increases when inflammation increases, especially in the heart and kidneys, and helps in converting ferrous iron into iron. The light subunit is present in the liver and spleen and has a role in storing iron (1). Coronavirus (COVID-19) caused by the new coronavirus SARS-CoV-2 is a disease It is new to humanity, as it is accompanied by symptoms during the disease, including blood abnormalities, with activation of the immune system and phagocytic monocytes, and damage to the lungs. In our study, we showed that ferritin is an indicator of the severity of the disease and mortality (2). Acute respiratory syndrome (Coronavirus), which causes pneumonia and damages the heart, liver, and kidneys, is caused by the appearance of acute inflammatory cytokines that lead to death (3). A cytokine is a small protein that transmits messages to help stimulate the body’s immune response, and its rise causes increased inflammation, and these Cytokines secreted by macrophages (TNF-α, IL-10, IL-6) where there is high inflammation in the plasma. An indicator of the progress and severity of the disease (3).